Persepsi Petani terhadap Program Kambojanisasi dalam Upaya Pengendalian Hama Terpadu Padi Ramah Lingkungan di Desa Jaten Kecamatan Jaten Kabupaten Karanganyar: Introduction, Research Methods, Results and Discussion, Conclusions, Reference List - Asna Nawalia (Jurnal Studi Inovasi, 2022)
Perception determines how a person makes decisions. In the world of agriculture, the perception of farmers is the basis where a program can be implemented properly. The implementation of the Kambojanisasi program is influenced by the perception of the farmers themselves. This study aims to describe the factors forming the perception of farmers on the Kambojanisasi program, examine the level of farmers' perceptions of the Kambojanisasi program, and examine the relationship between the perception-forming factors and the level of farmers' perceptions of the Kambojanisasi program. The basic research method used is quantitative with survey techniques. The research location was chosen by purposive method in Jaten Village, Jaten District, Karanganyar Regency. Sampling using proportional random sampling technique and respondents were taken as many as 50 farmers. Data analysis used rank matcher correlation test (rs) with SPSS Statistics 25.0 program. The results showed that: (1) perception-forming factors, namely age, formal education, non-formal education, experience, land area, social environment and economic environment (2) perception of convenience dominated the level of farmers' perceptions of the Kambojanisasiization program in Jaten Village, namely in the category good. (3) There is a very significant relationship between the factors of age, formal education and experience with farmers' perceptions of the Kambojanisasi program, while non-formal education factors, land area, social environment and economic environment are not significantly related to farmers' perceptions of the Kambojanisasi program in Jaten Village.